2017
DOI: 10.1161/jaha.117.005505
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Recovery and Risk of Cardiovascular Events and All‐Cause Mortality: A Meta‐Analysis of Prospective Cohort Studies

Abstract: BackgroundHeart rate recovery (HRR) is a noninvasive assessment of autonomic dysfunction and has been implicated with risk of cardiovascular events and all‐cause mortality. However, evidence has not been systematically assessed. We performed a meta‐analysis of prospective cohort studies to quantify these associations in the general population.Methods and ResultsA literature search using 3 databases up to August 2016 was conducted for studies that reported hazard ratios with 95% CIs for the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(171 citation statements)
references
References 50 publications
3
147
2
5
Order By: Relevance
“…Observational studies have shown strong associations of HR-recovery and HRincrease with sudden cardiac death, all-cause death, cardiovascular death 4,5,46 and even cancer 49 . These studies all suggested that autonomic impairment, the imbalance of vagal and adrenergic tone, increases the susceptibility to disease and mortality, and (although never shown) life-threatening arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies have shown strong associations of HR-recovery and HRincrease with sudden cardiac death, all-cause death, cardiovascular death 4,5,46 and even cancer 49 . These studies all suggested that autonomic impairment, the imbalance of vagal and adrenergic tone, increases the susceptibility to disease and mortality, and (although never shown) life-threatening arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…To explore potential clinical relevancy, polygenic scores were constructed based on the genome wide significant SNPs. The primary outcome variable was parental age as proxy for cardiovascular-and all-cause mortality 14,46 . The choice of disease outcomes and phenotypes was based on the previous studies of HR-response to exercise in relation to ventricular arrhythmia (sudden death 4 ), atrial fibrillation 47 , diabetes 48 , cancer 49 , or the importance of autonomic (dys)function in blood pressure 14 , reaction time, fluid intelligence 50 and depression 51 .…”
Section: Insights Into Pleiotropy and Clinical Relevancymentioning
confidence: 99%
“…): first author; publication year; geographical region; proportion of men; sample size; mean age; mean BMI; mean resting or peak heart rate; mean fasting glucose concentration; follow‐up period; methods for assessment of HRR and ascertainment of diabetes; number of person‐years (for dose–response analysis); HR and 95% CIs for the association; and adjusted variables. In studies that used several adjustment models for potential confounders, the most completely adjusted HR was selected for the primary analysis . When multiple publications were available for a single study from the same cohort, priority of selection was given to the one with the longest follow‐up period .…”
Section: Methodsmentioning
confidence: 99%
“…There is a large amount of evidence suggesting that autonomic dysfunction, as signified by attenuated HRR, is associated with increased risks of cardiovascular events and all‐cause mortality in the general population, and this appears to be independent of traditional cardiovascular risk factors . Recently, several lines of evidence have also pointed out that attenuated HRR may herald the development of diabetes and might carry prognostic power in predicting the risk of diabetes; on the one hand, autonomic dysfunction is often present in people with newly diagnosed diabetes and on the other hand, autonomic dysfunction will theoretically lead to an insufficient insulin secretion in response to elevated circulating glucose levels because of the potentially impaired capability of parasympathetic fibres in stimulating the pancreatic β cells to release insulin .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a marked interest has emerged in the clinical evaluation of the cardiac autonomic functions and cardiorespiratory fitness. Heart rate recovery (HRR) after graded exercise is one of the commonly used techniques which reflect autonomic activity and are positively correlated with cardiovascular fitness indices such as maximum oxygen uptake and endurance capacity . HRR is defined as heart rate difference between the maximal heart rate on exercise and the heart rate during recovery phase .…”
mentioning
confidence: 99%